Is there an information channel of monetary policy? - Oliver Holtemöller; Alexander Kriwoluzky; Boreum Kwak (Halle Institute for Economic Research (IWH), 2024)
Exploiting the heteroscedasticity of the changes in short-term and long-term interest rates and exchange rates around the FOMC announcement, we identify three structural monetary policy shocks. We eliminate the predictable part of the shocks and study their effects on financial variables and macro variables. The first shock resembles a conventional monetary policy shock, and the second resembles an unconventional monetary shock. The third shock leads to an increase in interest rates, stock prices, industrial production, consumer prices, and commodity prices. At the same time, the excess bond premium and uncertainty decrease, and the U.S. dollar depreciates. Therefore, this third shock combines all the characteristics of a central bank information shock.
Keywords: C36; E52; E58; 330; central bank information shock; high-frequency identication; identication through heteroskedasticity; monetary policy; proxy SVAR